Translation, psychometric evaluation, and network analysis of the parental acceptance and action questionnaire (PAAQ) among Arab parents of children with and without specific learning disability (dyslexia) - Norah Alkhateeb (Acta Psychologica)
Objective: The current study evaluated psychometric properties and network analysis of the Parental Acceptance and Action Questionnaire (PAAQ) among Arab parents of children with and without dyslexia. Method: 419 parents of community sample children and 318 parents of children with dyslexia (CWD) completed the PAAQ, Interpersonal Mindfulness Scale (IMS), and a socio-demographic checklist. Exploratory Graph Analysis (EGA), Confirmatory Factor Analysis (CFA), and Exploratory Factor Analysis (EFA) were used to determine the factor structure of the PAAQ. Cronbach's alpha was used to estimate internal consistency. Finally, the centrality measures are derived from network theory (betweenness, closeness, and strength). Results: In both community and CWD samples, the author identified similar factor structures encompassing three dimensions: proactive behavior and adaptability in parenting, acceptance of personal parenting-related inner experiences, and acceptance of the child's negative inner experiences. Item 18 was removed due to poor factor loading in both samples, resulting in a final version of the PAAQ with 18 items (instead of 19 items). This factor structure was revealed through EFA analysis and confirmed by CFA and GFA, demonstrating the scale's consistency. For all subscales in both samples, Cronbach's alpha was more significant than 0.7, indicating suitable internal consistency. Regarding centrality, both the community and dyslexia groups had similar centrality measures in some items. However, the dyslexia group generally showed higher betweenness values than the community group in several items (e.g., PAAQ.6, PAAQ.7). Conclusion: The PAAQ is a suitable scale for use with Arabic parents, including community samples and parents of children with dyslexia.